Five doubly unsaturated metabolites of valproic acid in urine and plasma of patients on valproic acid therapy - Kochen, Walter; Sprunck, H P; Tauscher, Bernhard; Klemens, Maria (Journal of clinical chemistry and clinical biochemistry, 1984)
The urine and plasma of epileptic patients receiving therapeutic doses of valproic acid (2-propyl- pentanoic acid) was found to contain five doubly unsaturated metabolites of valproic acid, which were identified as their trimethylsilyl derivatives by GC/MS. A series of reference substances was synthesized but only two of them were identical with native metabolites: 2(2-propenyl)-4-pentenoic acid (= 4.4'-diene) and E-2-propyl-2.4- pentadienoic acid (E-2.4-diene). The mass-spectra of the five native metabolites are given. Preliminary quantitative data obtained from four groups of patients indicate increased formation of doubly unsaturated metabolites when valproic acid-induced side-effects are present, and in cases of fatal hepatic failure. The 4.4'-diene has hitherto been found only in fatal cases with hepatic injury. Quantitative data are presented as % of the sum of valproic acid plus all its detected metabolites.